The electronic library model to support a «blended learning» system at Novosibirsk State University - A. M. Fedotov; T. S. Vasyuchkova; M. A. Derzho; N. A. Ivancheva; O. A. Fedotova (Библиосфера)
A technological approach for developing a digital library model to support the blended learning in Novosibirsk State University is considered in the article. The term «digital library» in this work is interpreted as an information management system of structured cataloged collections of interactive training and reference materials. The information system architecture, principles of integration with digital repository and rules of metadata representation and transformation are described. A special emphasis is paid on the activity with key terms dictionaries used for information resources systematization and classification, and modeling relations to the facts.